Reversal of ABCG2-mediated drug resistance by tinodasertib (ETC-206) - Yang, Haigan; Li, Zheshen; Wu, Zhuoxun; Chen, Xiang; Bo, Letao; Patel, Harsh; Zhang, Bohan; Xiong, Wenjun; Wang, Wei; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2025)
IntroductionMultidrug resistance (MDR) in cancer therapy, frequently driven by overexpression of ATP-binding cassette (ABC) transporters—particularly ABCG2—continues to undermine the efficacy of chemotherapeutic regimens. Tinodasertib (ETC-206), a selective ATP-competitive MNK1/2 kinase inhibitor, currently in Phase II clinical trials, has not yet been evaluated for its capacity to counteract ABCG2-mediated drug efflux. This study investigates whether tinodasertib can reverse ABCG2-dependent MDR in both two-dimensional (monolayer) cancer cell cultures and three-dimensional multicellular tumor spheroids.Materials and MethodsABCG2-overexpressing cancer cell lines and their nonresistant parental counterparts were cultured as monolayers and as multicellular spheroids. Cell viability analysis in the presence or absence of tinodasertib was performed by MTT assay. Western blotting and immunofluorescence studies assessed ABCG2 protein expression and subcellular localization following tinodasertib exposure. ATPase activity of purified ABCG2 was measured in the presence of increasing tinodasertib concentrations. In silico docking simulations were conducted to model tinodasertib binding to the ABCG2 transmembrane region.ResultsIn monolayer cultures, co-administration of tinodasertib significantly sensitized ABCG2-overexpressing cells to mitoxantrone and topotecan. Similar enhancement of cytotoxicity was observed in multicellular tumor spheroids, where tinodasertib reduced the spheroid growth when combined with ABCG2 substrates (p < 0.05). Western blot and immunofluorescence analyses showed no change in total ABCG2 protein levels or its membrane localization upon tinodasertib treatment. ATPase assays revealed a dose-dependent inhibition of ABCG2 ATP hydrolysis (IC50 ≈ 2 μM for ATPase activity). Docking studies predicted high-affinity binding of tinodasertib within the substrate-binding cavity of ABCG2, consistent with competitive inhibition of ATPase function.DiscussionThese data indicate that tinodasertib effectively reverses ABCG2-mediated MDR by blocking the transporter’s ATPase-dependent efflux mechanism without altering ABCG2 expression or trafficking. The concordance between ATPase inhibition and in silico docking supports a model wherein tinodasertib occupies the substrate-binding pocket of ABCG2, preventing ATP hydrolysis and subsequent drug transport. Overall, combining tinodasertib with ABCG2 substrate chemotherapeutics may represent a promising strategy for overcoming MDR in tumors overexpressing ABCG2, warranting further in vivo validation and clinical evaluation.